Entropy Bottlenecks at T->0 in Ce-Lattice and Related Compounds - Sereni, J.G.; Sereni, Julián (Springer, 2015)
Fil: Sereni, J. G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina